2018
DOI: 10.1017/jfm.2018.577
|View full text |Cite
|
Sign up to set email alerts
|

On the over-production of turbulence beneath surface waves in Reynolds-averaged Navier–Stokes models

Abstract: In previous computational fluid dynamics studies of breaking waves, there has been a marked tendency to severely over-estimate turbulence levels, both pre- and post-breaking. This problem is most likely related to the previously described (though not sufficiently well recognized) conditional instability of widely used turbulence models when used to close Reynolds-averaged Navier–Stokes (RANS) equations in regions of nearly potential flow with finite strain, resulting in exponential growth of the turbulent kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
195
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(223 citation statements)
references
References 57 publications
22
195
2
4
Order By: Relevance
“…Of these models, CFD models based on full solution of the Reynolds Averaged Navier Stokes equations are most analogous to the present SPH simulations as they both can directly resolve overturning breaking waves. In the context of recent applications of high-resolution mesh-based CFD models (i.e., OpenFOAM) that have been applied to the same experimental test cases (e.g., Larsen and Fuhrman, 2018, Brown et al, 2016, Jacobsen et al, 2012, the present results indicate that the SPH approach can reproduce these surf zone processes with comparable skill. In fact, the results of this work suggest that the SPH approach can help to improve predictions within the crest region of breaking waves, as evident by robust predictions of crossshore mass fluxes and undertow profiles that have been notoriously difficult to predict in meshbased CFD models.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…Of these models, CFD models based on full solution of the Reynolds Averaged Navier Stokes equations are most analogous to the present SPH simulations as they both can directly resolve overturning breaking waves. In the context of recent applications of high-resolution mesh-based CFD models (i.e., OpenFOAM) that have been applied to the same experimental test cases (e.g., Larsen and Fuhrman, 2018, Brown et al, 2016, Jacobsen et al, 2012, the present results indicate that the SPH approach can reproduce these surf zone processes with comparable skill. In fact, the results of this work suggest that the SPH approach can help to improve predictions within the crest region of breaking waves, as evident by robust predictions of crossshore mass fluxes and undertow profiles that have been notoriously difficult to predict in meshbased CFD models.…”
Section: Resultssupporting
confidence: 51%
“…Brown et al (2016) were able to improve predictions of the undertow profiles by adopting more sophisticated turbulence closure schemes (for example, see Figures 5 and 8 in Brown et al (2016) for comparisons with the spilling and plunging cases, respectively); however, in all cases the model overpredicted the undertow velocities more than in the present study, especially within the inner surf zone region where agreement with the SPH results were excellent. Larsen and Fuhrman (2018) observed similar overpredictions of the undertow in their CFD simulations, which they believed was due to surface rollers travelling too fast due to local underpredictions of eddy viscosities (hence flow resistance) simulated within the upper-most part of the water column, leading to increased onshore flows above the wave trough and increased return flows below the wave trough. While the undertow profiles were generally accurately predicted using the present SPH approach, the small discrepancies observed could likewise be due to some deviations in the vertical turbulent flow structure predicted within the inner surf zone.…”
Section: Wave-driven Transport and Surf Zone Turbulencementioning
confidence: 77%
See 2 more Smart Citations
“…It will be shown that the new stabilized closure eliminates entirely the wide-spread problem of over-predicted pre-breaking turbulence, with corresponding major qualitative improvements in the preto-post breaking evolution of the undertow profiles. Further details are provided in Larsen & Fuhrman (2018).…”
Section: Simulation Of a Simple Stream Function Wavementioning
confidence: 99%